2022
DOI: 10.3389/frai.2022.876007
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Prediction in Cardiac Intensive Care Unit Patients: A Systematic Review of Existing and Artificial Intelligence Augmented Approaches

Abstract: The medical complexity and high acuity of patients in the cardiac intensive care unit make for a unique patient population with high morbidity and mortality. While there are many tools for predictions of mortality in other settings, there is a lack of robust mortality prediction tools for cardiac intensive care unit patients. The ongoing advances in artificial intelligence and machine learning also pose a potential asset to the advancement of mortality prediction. Artificial intelligence algorithms have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The complexity as well as the severity of the patients admitted in CICUs makes this population quite special and requires personalized management based on several parameters mainly clinical, electrocardiographic, biological, and echocardiographic, in order to stratify the severity of these patients to predict the prognosis. With the evolution of artificial intelligence, it has been shown that several automated and dynamically evaluated algorithms can predict the evolution during hospitalization in CICU in a pertinent way (72).…”
Section: Artificial Intelligence (Ai) In Cicusmentioning
confidence: 99%
“…The complexity as well as the severity of the patients admitted in CICUs makes this population quite special and requires personalized management based on several parameters mainly clinical, electrocardiographic, biological, and echocardiographic, in order to stratify the severity of these patients to predict the prognosis. With the evolution of artificial intelligence, it has been shown that several automated and dynamically evaluated algorithms can predict the evolution during hospitalization in CICU in a pertinent way (72).…”
Section: Artificial Intelligence (Ai) In Cicusmentioning
confidence: 99%
“…AI has been widely applied in various fields, including sepsis detection and mortality prediction in ICUs. [13][14][15] However, most previous studies in this area have relied on retrospective medical record review. [16][17][18] It is important to note that there are poor correlations between non-real-time features and weaning outcomes at the time of extubation.…”
Section: Ai and Improvement In Healthcarementioning
confidence: 99%
“…AI will enable us to (1) differentiate congestive heart failure from other causes of lung disease and to quantify the amount of pulmonary edema secondary to it, using process imaging data; (2) identify left ventricular systolic dysfunction using AI-electrocardiogram and reduce mortality in CICU patients and (3) identify disease phenotypes or endotypes, which can inform personalized management and clinical trials. 44,45 These AI-research driven advances, in addition to many others, herald a new age of patient care in the ICUs.…”
Section: Brave New World Of Cardiac Icusmentioning
confidence: 99%